CORRELATION OF VARIOUS ENVIRONMENTAL FACTORS TO COFFEE LEAF RUST DISEASE AND ITS NATURAL CONTROL - Nur Kholida; Nur Prihatiningsih; Endang Mugiastuti; Endang Mugiastuti; Siti Nurchasanah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Climate is an important factor in the development of plant diseases. to be able to avoid yield loss due to disease explosion, it is necessary to conduct an in-depth study of climatic factors as a direct and indirect influence. one that can be done is weather data-based forecasting. This method can determine and estimate the likelihood of disease outbreaks in a certain period. In addition, disease forecasting can act as prevention due to pathogen attacks so as to avoid damage and yield loss and maintain the ecosystem of antagonistic fungi in the coffee ecosystem. Agro ecosystem management can encourage the development of antagonistic fungi as pathogen biological agents. Akanthomyces sp. species are widely reported as entomopathogenic fungi. In Indonesia, Akanthomyces sp. was found to be associated with Arabica coffee leaf rust disease. This study was conducted in seven coffee plantation locations in Kalibening District, Banjarnegara Regency, Indonesia. This study detected environmental factors affecting the development of Hemileia vastatrix, predicted its population and determined the antagonistic fungus associated with H. vastatrix, namely Akanthomyces sp. TBK2, by molecular detection.